Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12885-015-1958-6
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol elicits anti-colorectal cancer effect by activating miR-34c-KITLG in vitro and in vivo

Abstract: BackgroundSilence of the tumor suppressor miR-34c is implicated in the development of colorectal cancer (CRC). For the past few years, Resveratrol (Res) has been introduced to oncotherapies alone or with traditional chemotherapeutic drugs. However, the study of molecular mechanism involved in the anti-CRC effect of Res is still ongoing.MethodsThe anti-CRC effect of Res alone or with Oxaliplatin (Oxa) was determined by cell viability assay, soft agar colony formation assay, flow cytometry and real-time cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…A broad spectrum of miRNAs has been identified to be involved in the etiology of AD and cancer. Among them, miR-34c, as a tumor suppressor and a critical mediator in the p53 pathway (Beard et al, 2016;Cortez et al, 2016), can reduce cell growth, induce apoptosis, and affect cell migration (Tao et al, 2016;Yang et al, 2015). It is reported that the levels of miR-34c were increased in circulating blood samples of patients with AD compared to age-matched normal controls (Bhatnagar et al, 2014) .…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of miRNAs has been identified to be involved in the etiology of AD and cancer. Among them, miR-34c, as a tumor suppressor and a critical mediator in the p53 pathway (Beard et al, 2016;Cortez et al, 2016), can reduce cell growth, induce apoptosis, and affect cell migration (Tao et al, 2016;Yang et al, 2015). It is reported that the levels of miR-34c were increased in circulating blood samples of patients with AD compared to age-matched normal controls (Bhatnagar et al, 2014) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RSV reduced the growth and bioluminescent signals of orthotopic colon tumor (COLO205-luc). In another study in xenograft mice, a combination of RSV and oxaliplatin was more effective at inhibiting tumor growth than RSV and oxaliplatin alone of implanted colon cancer [29,30].…”
Section: Discussionmentioning
confidence: 95%
“…A research by Feng demonstrated that RSV significantly inhibited cell proliferation of colon cancer cells (HCA-17, SW480, HT29) cells by inducing apoptosis and inhibiting expression of cyclooxygenase-2 and prostaglandin receptor [82]. Yang found that RSV suppressed colorectal cancer by upregulating miR-34c which successively was able to inhibit its target KITLG, this effect was accentuated in presence of p53 compared to p53-knockdown cells in vitro and in vivo [83]. RSV significantly showed anti-cancer effect by upregulating expression level of BMP9 in LoVo cells, moreover, via mitochondria apoptosis pathway triggered by production of ROS [101].…”
Section: Resveratrol and Colorectal Cancermentioning
confidence: 99%